2018
DOI: 10.1038/s41390-018-0030-z
|View full text |Cite
|
Sign up to set email alerts
|

LPS-induced maternal inflammation promotes fetal leukocyte recruitment and prenatal organ infiltration in mice

Abstract: LPS-induced maternal endotoxemia promotes IUFD, PTB, and fetal leukocyte recruitment depending on gestational age. Our proposed model may serve as a platform to test novel perinatal immune modulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 31 publications
4
40
0
Order By: Relevance
“…Our data agrees with several other reports of LPS-induced inflammation and PTB in a mouse model [ 61 , 62 , 63 ]. In addition, we report that this inflammation is also associated with elevated NHERF1.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our data agrees with several other reports of LPS-induced inflammation and PTB in a mouse model [ 61 , 62 , 63 ]. In addition, we report that this inflammation is also associated with elevated NHERF1.…”
Section: Discussionsupporting
confidence: 94%
“…Typically, NHERF1 is a PDZ-scaffolding protein that organizes functional complexes and modulates kinase activities to accurately coordinate specific signaling pathways [ 59 ]. Previous studies have shown that NHERF1 expression is increased in inflammatory carcinogenic tissues [ 60 , 61 ]. Similarly, we observed higher NHERF1 gene expression in human fetal membranes from TL and PTB that are triggered by inflammation compared to membranes not in labor.…”
Section: Discussionmentioning
confidence: 99%
“…[61][62][63] Thus, even in the absence of fetal viral infection or severe maternal symptoms, placental infection can trigger a fetal inflammatory response, leading to multiorgan system damage and predisposition for negative developmental consequences (Table 2). [64][65][66][67][68][69][70] There is strong evidence to suggest that maternal inflammation associated with SARS-CoV-2 may confer long-term risk of neuropsychiatric disorders in children. MIA has been described as a "neurodevelopmental disease primer" that increases susceptibility of individuals to interacting genetic and environmental risk factors that can trigger neuro-or psychopathology later in life.…”
Section: Discussionmentioning
confidence: 99%
“…Although IA inflammation is restricted to the fetal-maternal interface and the amniotic fluid, pathogenassociated IA inflammation leads to inflammatory responses in multiple other fetal organs including the brain, lungs, skin, and gut in humans and animals (5,6). Much of the work investigating infection-driven inflammation at the fetal-maternal interface has focused on the maternally derived decidua and/or the fetus-derived fetal membranes (7)(8)(9)(10)(11). Yet, the fetus-derived placental villi, which is in contact with the fetal membranes and invades into the maternal decidua, comprises the bulk of the fetal-maternal interface by mass.…”
Section: Introductionmentioning
confidence: 99%